The doctrine of the lesser magistrates : a proper resistance to tyranny and a repudiation of unlimited obedience to civil government - Trewhella, Matthew J. ([Place of publication not identified] : CreateSpace, 2013)
"America has entered troubling times. The rule of law is crumbling. The massive expansion of Federal government power with its destructive laws and policies is of grave concern to many. But what can be done to quell the abuse of power by civil authority? Are unjust or immoral actions by the government simply to be accepted and their lawless commands obeyed? How do we know when the government has acted tyrannically? Which actions constitute proper and legitimate resistance? This book places in your hands a hopeful blueprint for freedom. Appealing to history and the Word of God, Pastor Matthew Trewhella answers these questions and shows how Americans can successfully resist the Federal government's attempts to trample our Constitution, assault our liberty, and impugn the law of God. The doctrine of the lesser magistrates declares that when the superior or higher civil authority makes an unjust/immoral law or decree, the lesser or lower ranking civil authority has both the right and duty to refuse obedience to that superior authority. If necessary, the lower authority may even actively resist the superior authority. Historically, this doctrine was practiced before the time of Christ and Christianity. It was Christian men, however, who formalized and embedded it into their political institutions throughout Western Civilization. The doctrine of the lesser magistrates is a historic tool that provides proven guidelines for proper and legitimate resistance to tyranny, often without causing any major upheaval in society. The doctrine teaches us how to rein in lawless acts by government and restore justice in our nation. "Use this sword against my enemies, if I give righteous commands; but if I give unrighteous commands, use it against me."--Roman Emperor Trajan, speaking to one of his subordinates This is the first book published solely addressing the doctrine of the lesser magistrates in over 400 years. Matthew Trewhella is the pastor of Mercy Seat Christian Church. He is a graduate of Valley Forge Christian College. He and his wife, Clara, have eleven children and nine grandchildren, and reside in the Milwaukee, Wisconsin area. His research and teaching on the lesser magistrate doctrine is reshaping the thinking of Americans. He was instrumental in publishing the Magdeburg Confession in 2012 - the first English translation of the document since it was written in 1550."--Back cover.
Keywords: Christianity and politics; Church and state; Christianity and politics; Church and state